Design and Implementation of TPACK-Based Differentiated Interactive Multimedia for Enhancing Pancasila Education in Elementary Schools - Bunga Aulia; Surya Dharma; Sriadhi Sriadhi (STAI Hubbulwathan Duri, 2025)
This study aimed to develop and evaluate TPACK-based interactive differentiated multimedia for Pancasila Education in Grade V elementary schools. The goal was to enhance students' understanding of the application of Pancasila values within family and school environments. Employing a Research and Development (RD) approach, the study followed the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation. Participants included content, language, and media experts; teachers of classes V-A and V-C; and 33 fifth-grade students at Alwashliyah Private Elementary School Rentang 80. The result of the development process was an interactive learning application based on TPACK principles and differentiated instruction. This multimedia resource could be accessed via laptops or smartphones, both online and offline. Expert validation confirmed its feasibility, with material experts rating it at 90.6%, language experts at 85%, and media experts at 95%, all categorized as